2014
DOI: 10.1155/2014/428989
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis Coli Mimicking Colorectal Cancer

Abstract: Pneumatosis coli (PC) is a rare condition of the gastrointestinal tract involving extraluminal gas confined within the bowel wall. We report the case of a 40-year-old gentleman presenting clinically and endoscopically with suspected colorectal cancer. In light of the patient's red flag symptoms, and carpet of polyps seen endoscopically, surgical management by an anterior resection was performed with the patient making a successful recovery. Histological analysis of the resected specimen confirmed pneumatosis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Primary or idiopathic PCI is a rare condition that accounts for only less than 15% of all the reported cases [2]. Although Idiopathic PCI can present with or without related intestinal symptoms, the literature review showed that most of the reported cases have presented with symptoms [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Primary or idiopathic PCI is a rare condition that accounts for only less than 15% of all the reported cases [2]. Although Idiopathic PCI can present with or without related intestinal symptoms, the literature review showed that most of the reported cases have presented with symptoms [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%